Plant-based elicitor improves nutrient efficiency and sustains rice yield under reduced fertilizer in a one-season field study - HARWANTO HARWANTO; ENY WAHYUNING PURWANTI; JOKO GAGUNG SUNARYONO; NIKEN RANI WANDANSARI (Asian Journal of Agriculture, 2026)
Abstract. Harwanto, Purwanti EW, Sunaryono JG, Wandansari NR. 2026. Plant-based elicitor improves nutrient efficiency and sustains rice yield under reduced fertilizer in a one-season field study. Asian J Agric 10 (1): g100179. https://doi.org/10.13057/asianjagric/g100179. Excessive dependence on chemical fertilizers raises environmental concerns and reduces long-term soil fertility. A plant-based elicitor containing bioactive compounds (flavonoids, phenols, tannins) and phytohormones (IAA, cytokinins, gibberellins) such as Biosaka, has been promising elicitors to enhance nutrient efficiency and crop resilience. A field experiment was conducted in East Java, Indonesia, using a randomized block design with five treatments: 100% inorganic fertilizer (control), 100% inorganic fertilizer + Biosaka, 75% inorganic fertilizer + Biosaka, 50% inorganic fertilizer + Biosaka, and 25% inorganic fertilizer + Biosaka. Each treatment was replicated four times. Variables measured included plant growth, yield components, straw nutrient content (N, P, K), and soil chemical properties (pH, organic C, available N, P, K). The combination of 50% inorganic fertilizer + Biosaka maintained straw nitrogen comparable to full fertilizer and resulted in higher straw phosphorus content. The combination of 100% inorganic fertilizer + Biosaka produced the highest straw Kalium (0.53%) and milled rice weight (454.41 g 2 m-2). Biosaka treatments were associated with higher soil pH (6.30), organic carbon (0.99%), and available N and K compared to non-Biosaka treatments. Biosaka supplements have not compensated for the nutrient deficiency in the treatments with excessive fertilizer reduction (≤25%). It resulted in lower nutrient content and reduced milled rice weight (265.09 g 2 m-2). This study provides novel evidence that integrating Biosaka treatment with 50% inorganic fertilizer can sustain rice yield equivalently to the conventional 100% inorganic fertilizer application.